Nuclear RNA-related processes modulate the assembly of cytoplasmic RNA granules - Angel, Mor; Fleshler, Eden; Atrash, Mohammad Khaled; Kinor, Noa; Benichou, Jennifer I C; Shav-Tal, Yaron (Nucleic acids research, 2024)
Stress granules (SGs) are cytoplasmic assemblies formed under various stress conditions as a consequence of translation arrest. SGs contain RNA-binding proteins, ribosomal subunits and messenger RNAs (mRNAs). It is well known that mRNAs contribute to SG formation; however, the connection between SG assembly and nuclear processes that involve mRNAs is not well established. Here, we examine the effects of inhibiting mRNA transcription, splicing and export on the assembly of SGs and the related cytoplasmic P body (PB). We demonstrate that inhibition of mRNA transcription, splicing and export reduces the formation of canonical SGs in a eukaryotic initiation factor 2α phosphorylation-independent manner, and alters PB size and quantity. We find that the splicing inhibitor madrasin promotes the assembly of stress-like granules. We show that the addition of synthetic mRNAs directly to the cytoplasm is sufficient for SG assembly, and that the assembly of these SGs requires the activation of stress-associated protein synthesis pathways. Moreover, we show that adding an excess of mRNA to cells that do not have active splicing, and therefore have low levels of cytoplasmic mRNAs, promotes SG formation under stress conditions. These findings emphasize the importance of the cytoplasmic abundance of newly transcribed mRNAs in the assembly of SGs. Graphical Abstract Graphical Abstract